THE ROLE OF PARENTS IN THE DEVELOPMENT OF STIMULATION MOTOR SMOOTH OF CHILDREN IN THE AGE OF 4-5 YEARS IN KECAMATAN PALANG KABUPATEN TUBAN - Sumasto, Hery (Health Notions, 2019)
Stimulation for children will create intelligent children, can grow and develop optimally, independently and emotionally stable can also adapt . Therefore, stimulation is very important especially at the age of 4-5 years in their first years (golden years) because it can create people who have good personality, intelligence, independence, ethics, skills and productivity. The purpose of this study was to determine the relationship of the role of parents in stimulating the fine motor development of children aged 4-5 years. The study design was a correlational study, the respondents of this study were children aged 4-5 years. The population is 169 respondents. The sampling technique uses proportional stratified random sampling. The independent variable is the role of parents in stimulation and the dependent variable is the smooth motor development of children aged 4-5 years. Data collection using questionnaires and observation sheets. Data analysis with logistic regression test. The results showed that the three variations in the role of parents did not have a significant effect on stimulation. The active role of parents for the development of children less than 5 years is very important. Conclusion: Parents must participate, provide opportunities to learn, to practice their fine motor skills and provide guidance in the formation of behavior and skills.